Original paperDose estimation for different skin models in interstitial breast brachytherapy - Lasota, Judyta; Kabacińska, Renata; Makarewicz, Roman (Journal of Contemporary Brachytherapy, 2014)
Purpose: Skin is a major organ at risk in breast-conserving therapy (BCT). The American Brachytherapy Society (ABS) recommendations require monitoring of maximum dose received, however, there is no unambiguous way of skin contouring provided. The purpose of this study was to compare the doses received by the skin in different models. Material and methods: Standard treatment plans of 20 patients who underwent interstitial breast brachytherapy were analyzed. Every patient had a new treatment plan prepared according to Paris system and had skin contoured in three different ways. The first model, Skin 2 mm, corresponds to the dermatological breast skin thickness and is reaching 2 mm into an external patient contour. It was rejected in a further analysis, because of distinct discontinuities in contouring. The second model, Skin 4 mm, replaced Skin 2 mm, and is reaching 2 mm inside and 2 mm outside of the External contour. The third model, Skin EXT, is created on the External contour and it expands 4 mm outside. Doses received by the most exposed 0.1 cc, 1 cc, 2 cc, and the maximum doses for Skin 4 mm and Skin EXT were compared. Results: Mean, median, maximum, and standard deviation of percentage dose difference between Skin EXT and Skin 4 mm for the most exposed 0.1 cc (D 0.1cc ) of skin were 18.01%, 17.20%, 27.84%, and 4.01%, respectively. All differences were statistically significant (p < 0.05). Conclusions : Monitoring of doses received by skin is necessary to avoid complications and obtain a satisfactory cosmetic effect. It is difficult to assess the compatibility of treatment plans with recommendations, while there is no unambiguous way of skin contouring. Especially, if a mean difference of doses between two models of skin contouring is 18% for the most exposed 0.1 cc and can reach almost 28% in some cases. Differences of this magnitude can result in skin complications during BCT.